EXPLORING DWELLING OVERCROWDING MEASURES: OBJECTIVE APPROACHES AND PERCEIVED CROWDING - Wong, Syu Yit; Azmi, Nur Farhana; Jin Lin Chua , Shirley (Journal of Surveying, Construction and Property, 2025)
Dwelling overcrowding is a complex issue not only measured by standard guidelines but also by subjective perceptions of crowding. It extends beyond physical dimensions to encompass human factors such as psychological and social experiences. While intervention policies often focus on addressing spatial constraints, integrating objective approaches with subjective measures can provide more effective and holistic solutions, especially in sustainable housing intervention. This study aims to address the complexity of dwelling overcrowding by reviewing existing objective approaches and exploring perceived crowding as a complementary measure. The methodologies used for this study are literature searches and review analysis, guided by standard guidelines from multiple countries. A comprehensive literature search with selection criteria focusing on overcrowding measures, contributing factors, and housing policies. The literature was categorized into three key themes: objective measures of overcrowding, perceived crowding as a subjective measure, and intervention strategies. Findings highlight the importance of integrating objective and subjective measures in housing policies to address both physical and experiential aspects of overcrowding. This study provides the foundation for evidence-based policy recommendations. Future research should test the variables through real-world case studies to assess factors influencing overcrowding and the effectiveness of proposed housing interventions.